Alternative Oxidase Activity and the Ubiquinone Redox Level in Soybean Cotyledon and Arum Spadix Mitochondria during NADH and Succinate Oxidation. - Hoefnagel, MHN. (1996)
In Arum and soybean (Glycine max L.) mitochondria, the dependence of the alternative oxidase activity on the redox level of ubiquinone, with NADH and succinate as substrates, was studied, using a voltametric procedure to measure the ubiquinone redox poise in the mitochondrial membrane. The results showed that when the enzyme was activated by pyruvate the relationship between the alternative oxidase rate and the redox state of the ubiquinone pool was the same for both NADH and succinate oxidations. In the absence of pyruvate the alternative oxidase had an apparent lower affinity for ubiquinol. This was more marked with NADH than with succinate and was possibly due to pyruvate production during succinate oxidation or to an activation of the alternative oxidase by succinate itself. In Arum spadix (unlike soybean cotyledon) mitochondria, succinate oxidation via the alternative oxidase maintained the ubiquinone pool in a partially reduced state (60%), whereas NADH oxidation kept it almost completely reduced. Previous data comparing mitochondria from thermogenic and nonthermogenic tissues have not examined the full range of ubiquinone redox levels in both tissues, leading to the suggestion that the activity of alternative oxidase for Arum was different from nonthermogenic tissues. When the complete range of redox states of ubiquinone is used and the oxidase is fully activated, the alternative oxidase from thermogenic tissue (Arum) behaves similarly to that of nonthermogenic tissue (soybean).